2007
DOI: 10.3348/kjr.2007.8.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Peliosis Hepatis with Hemorrhagic Necrosis and Rupture: a Case Report with Emphasis on the Multi-Detector CT Findings

Abstract: We report here on an uncommon case of peliosis hepatis with hemorrhagic necrosis that was complicated by massive intrahepatic bleeding and rupture, and treated by emergent right lobectomy. We demonstrate the imaging findings, with emphasis on the triphasic, contrast-enhanced multidetector CT findings, as well as reporting the clinical outcome in a case of peliosis hepatis with fatal hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 8 publications
(24 reference statements)
2
19
0
Order By: Relevance
“…Adam et al [17] and Toth et al [18] reported cases of PH rupture located in the left lobe of liver. But in other cases, the right lobe of the liver was the location of rupture [9,[19][20][21][22] , including the current case. Although Saatci et al [23] reported a case of PH with multiple foci involving both right and left lobes by magnetic resonance imaging, the location of PH in most cases was unilobar, which may be explained by the distribution of hepatic blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Adam et al [17] and Toth et al [18] reported cases of PH rupture located in the left lobe of liver. But in other cases, the right lobe of the liver was the location of rupture [9,[19][20][21][22] , including the current case. Although Saatci et al [23] reported a case of PH with multiple foci involving both right and left lobes by magnetic resonance imaging, the location of PH in most cases was unilobar, which may be explained by the distribution of hepatic blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of hemorrhage, PH lesions appear as hyperattenuating structures on unenhanced CT. Hepatic angiography discloses a typical appearance of PH lesions that accumulate contrast in the late arterial or parenchymal phase and retain it through the early venous phase. [7,8] In our patient, an abdomen CT scan showed hepatomegaly with heterogeneous enhancement of liver parenchyma. A Liver biopsy is the most rewarding tool in diagnosing PH.…”
Section: Case Reportmentioning
confidence: 99%
“…Prognosis is largely determined by the underlying cause and is generally guarded. [6][7][8][9][10] Herein, we present a case of a young female presenting in her seventh month of gestational amenorrhea with signs of portal hypertension and subsequently diagnosed to have PH.…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties have been associated with making a definite preoperative diagnosis of well‐differentiated PHCC on imaging including ultrasound, computed tomography (CT), and magnetic resonance imaging (MRI) scans …”
Section: Introductionmentioning
confidence: 99%